Studies on Soundscapes of Polish Cities: The Case of Wroclaw - Muszkalska, Bożena (Lidé města, 2012)
The soundscape of cities is a subject of research of various disciplines, e.g., acoustics, cultural anthropology, landscape architecture, geography, urban studies, sociology, musicology. Whereas the representatives of other sciences concentrate on non-musical phonic elements which co-create the audio sphere of towns, phenomena of the so-called melosphere or the characteristic, significant sphere, singled out by men from the sound background, are in the center of interest of musicologists. The aspect of significance in the above definition has a strict musical reference, but also a social one. It concerns significances and values of the melosphere as cultural transmission. Research on these phenomena covers not only its documentation but also an identification of the phonic identity of the city. Studies on functional and axiological aspects of musical sounds in the city space require taking into consideration their reception by inhabitants of the town which is examined through interviews.